The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/978-3-540-69057-3_31
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Perceptual Representations of Complex, Parametrically-Defined Shapes Using MDS

Abstract: Abstract. In this study we show that humans are able to form a perceptual space from a complex, three-dimensional shape space that is highly congruent to the physical object space no matter if the participants explore the objects visually or haptically. The physical object space consists of complex, shell-shaped objects which were generated by varying three shape parameters. In several psychophysical experiments participants explored the objects either visually or haptically and performed similarity ratings. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 14 publications
(25 reference statements)
1
9
0
Order By: Relevance
“…More recently, however, a series of studies has systematically compared visual and haptic categorization. Using multi-dimensional scaling analysis, these studies showed that visual and haptic similarity ratings and categorization result in perceptual spaces [i.e., topological representations of the perceived (dis)similarity along a given dimension] that are highly congruent between modalities for novel 3-D objects ( Cooke et al, 2007 ), more realistic 3-D shell-like objects ( Gaißert et al, 2008 , 2010 , 2011 ) and for natural objects, i.e., actual seashells ( Gaißert and Wallraven, 2012 ). This was so in both unisensory and bisensory conditions ( Cooke et al, 2007 ) and whether 2-D visual objects were compared to haptic 3-D objects ( Gaißert et al, 2008 , 2010 ) or passive viewing of 2-D objects was compared to interactive viewing and active haptic exploration of 3-D objects, i.e., such that visual and haptic exploration were more similar ( Gaißert et al, 2010 ).…”
Section: Object Categorizationmentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, however, a series of studies has systematically compared visual and haptic categorization. Using multi-dimensional scaling analysis, these studies showed that visual and haptic similarity ratings and categorization result in perceptual spaces [i.e., topological representations of the perceived (dis)similarity along a given dimension] that are highly congruent between modalities for novel 3-D objects ( Cooke et al, 2007 ), more realistic 3-D shell-like objects ( Gaißert et al, 2008 , 2010 , 2011 ) and for natural objects, i.e., actual seashells ( Gaißert and Wallraven, 2012 ). This was so in both unisensory and bisensory conditions ( Cooke et al, 2007 ) and whether 2-D visual objects were compared to haptic 3-D objects ( Gaißert et al, 2008 , 2010 ) or passive viewing of 2-D objects was compared to interactive viewing and active haptic exploration of 3-D objects, i.e., such that visual and haptic exploration were more similar ( Gaißert et al, 2010 ).…”
Section: Object Categorizationmentioning
confidence: 99%
“…Using multi-dimensional scaling analysis, these studies showed that visual and haptic similarity ratings and categorization result in perceptual spaces [i.e., topological representations of the perceived (dis)similarity along a given dimension] that are highly congruent between modalities for novel 3-D objects ( Cooke et al, 2007 ), more realistic 3-D shell-like objects ( Gaißert et al, 2008 , 2010 , 2011 ) and for natural objects, i.e., actual seashells ( Gaißert and Wallraven, 2012 ). This was so in both unisensory and bisensory conditions ( Cooke et al, 2007 ) and whether 2-D visual objects were compared to haptic 3-D objects ( Gaißert et al, 2008 , 2010 ) or passive viewing of 2-D objects was compared to interactive viewing and active haptic exploration of 3-D objects, i.e., such that visual and haptic exploration were more similar ( Gaißert et al, 2010 ). These highly similar visual and haptic perceptual spaces both showed high fidelity to the physical object space [i.e., a topological representation of the actual (dis)similarity along a given dimension; Gaißert et al, 2008 , 2010 ], retaining the category structure (the ordinal adjacency relationships within the category, i.e., the actual progression in variation along a given dimension, for example from roughest to smoothest; Cooke et al, 2007 ).…”
Section: Object Categorizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In an early use of haptic MDS, Hollins et al tested perception of 17 real tactile surface textures through sorting [30] and derived a 3D solution space; this group has also found "substantial but not complete" agreement in stimulus organization between individuals [29]. More recently, MDS has been used to measure user organization of tactile melodies [58] and complex shapes [19].…”
Section: Mds Tool To Visualize Structure and Optimize Spacingmentioning
confidence: 99%